The implementation of the universal jurisdiction over torture in European countries - Coppée, Tom Jean G (Department of Public Law, 2016)
This dissertation presents an evaluation of universal jurisdiction over torture offenses. By doing so, it focuses on European states, in particular Belgium, France and the United Kingdom, all of which show a particular openness to prosecute torture offences on the basis of universal jurisdiction. It is demonstrated that Belgium, France and the United Kingdom have complied with the obligation set out in article 5(2) of the UN Torture Convention to establish universal jurisdiction over torture offences in their domestic legislation. They were, moreover, the first countries to conduct torture trials on this ground. However, 30 years after the signature of the Convention, such trials rarely occur because European prosecutors and courts face both practical and legal problems. I argue that some controversies have been solved, especially those relating to the non-retroactivity of the implemented legislation, the prohibition of amnesties, as well as the legality of the proceedings in the absence of the offender and of the operation of a principle of subsidiarity. The latter principle would give primacy jurisdiction at least to the territorial state that wants and is able to prosecute. However, the controversies relating to the legality of the universal jurisdiction over the torture of citizens of non States Parties, the ne bis in idem prohibition, the broad immunities and the establishment of efficient legislation and cooperation between states are far from being settled. I argue that the cooperation between states at the regional and international level is needed to solve the legal and practical issues about universal jurisdiction over torture, and to stop its differentiated applications. The forum state is also responsible to provide prosecution and police services with a suitable working context that has clear and efficient legislation and guidelines about universal jurisdiction over torture. Indeed, successful prosecution primarily devolve to these criminal practitioners' motivation.